2023
DOI: 10.3389/fimmu.2023.1266461
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial antiviral signaling protein: a potential therapeutic target in renal disease

Meng Wu,
Zhiyin Pei,
Guangfeng Long
et al.

Abstract: Mitochondrial antiviral signaling protein (MAVS) is a key innate immune adaptor on the outer mitochondrial membrane that acts as a switch in the immune signal transduction response to viral infections. Some studies have reported that MAVS mediates NF-κB and type I interferon signaling during viral infection and is also required for optimal NLRP3 inflammasome activity. Recent studies have reported that MAVS is involved in various cancers, systemic lupus erythematosus, kidney diseases, and cardiovascular disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 111 publications
0
2
0
Order By: Relevance
“…RIG-I and MDA5 both activate the MAVS pathway upon filamentation and the subsequent ubiquitination and oligomerization of their two N-terminal CARD domains ( Peisley et al, 2012 ; Peisley et al, 2013 ). MAVS recruits TRAF3/6 which subsequently activates the kinase complexes TBK1 and IKK, which in turn leads to activation of IRF3/7 and NF-κB, respectively ( Wu et al, 2023 ). While the downstream signaling cascades of the two receptors are very similar, the dsRNA species that they each recognize are distinct.…”
Section: Ivt Byproducts and Their Biological Impactsmentioning
confidence: 99%
“…RIG-I and MDA5 both activate the MAVS pathway upon filamentation and the subsequent ubiquitination and oligomerization of their two N-terminal CARD domains ( Peisley et al, 2012 ; Peisley et al, 2013 ). MAVS recruits TRAF3/6 which subsequently activates the kinase complexes TBK1 and IKK, which in turn leads to activation of IRF3/7 and NF-κB, respectively ( Wu et al, 2023 ). While the downstream signaling cascades of the two receptors are very similar, the dsRNA species that they each recognize are distinct.…”
Section: Ivt Byproducts and Their Biological Impactsmentioning
confidence: 99%
“…This causes the activation and recruitment of NLR family pyrin domain containing 3 (NLRP3). Wu et al have reported that MAVS mediates NF-kB and type I interferon signaling during viral infection and is also required to activate the NLR family pyrin domain containing 3 (NLRP3) that triggers an immune response (55).. Apoptosisassociated speck-like protein containing a caspase recruitment domain (ASC) protein (56), and Caspase-1, which assemble to create the NLRP3 inflammasome (57). The activated NLRP3 inflammasome cleaves the cytokines Pro-IL-1B and Pro-IL-18 into their mature and biologically active forms (IL-1B and IL-18), thus exacerbating the inflammation state (58).…”
Section: Covid-19 Virus Influences Mitochondria Of the Infected Patientmentioning
confidence: 99%